Multi-criteria techniques based proposals for the End of Childhood Index: reference levels and compensation issues. - El-Gibari-Ben-Said, Samira; Gómez-Núñez, Trinidad; Cabello-González, José Manuel; Ruiz-de-la-Rúa, Francisco (Elsevier, 2024)
Child well-being is a subject of paramount importance, since a careful analysis of all the aspects related to childhood may have a major impact on the society as a whole. In this paper, based on the End of Childhood Index, which is a fully compensatory composite indicator published annually by the international organisation Save the children, we analyse the added information that can be provided through the use of multi-criteria analysis techniques. On the one hand, rather than analysing the overall performance of the countries by the use of the fully compensatory scenario, we make use of the international reference levels and performance bands provided by Save the Children itself, allowing to measure the distance of each country with respect to these levels. Besides, the use of a non-compensatory scenario offers interesting insights about the possible imbalances of each country, which is helpful in decision making processes. First, based on the data of the last available year, 2021, an overview of the worldwide analysis and a further detailed single region analysis is carried out. Second, a dynamic analysis over a period of five years (2017-2021) is undertaken. In this line, in order to guide childhood decision makers towards the identification of possible opportunities for improvement and the implementation of the corresponding action plans, the multiple reference point technique makes it possible to analyse the compliance in each one of the indicators, based on the use of distance reference levels and the joint consideration of a fully and non-compensatory composite indicators.
Keywords: Optimización matemática; Niños - Protección, asistencia, etc.; Performance bands; Composite indicators; Compensation; Multi-criteria techniques; Childhood